1 × N (N = 2, 8) Silicon selector switch for prospective technologies at the 2 μm waveband - Sia, Brian Jia Xu (2021)
The 2 μm waveband, specifically near 1.9 μm, is an imperative resource that could possibly be exploited in future communications systems. This is due to the promising infrastructural developments at the wavelength region (hollow-core photonic bandgap fiber, thulium-doped fiber amplifier) near 1.9 μm. In this work, we report the 1 × N selector switch based on Mach-Zehnder interferometers operating near the 1.9 μm wavelength region. As an elementary cell (N = 2), an insertion loss as low as 1.1 dB, P π of 23 mW, 10-90% switching time of lower than 38 μs and a crosstalk of lower than -25 dB from 1880 to 1955 nm has been determined. In order to prove scalability, the 1 × 8 switch (N = 8) is demonstrated, indicating crosstalk as low as -21 dB, considering all possible switching configurations across the abovementioned wavelength region. Insertion loss levels are examined.